Smoking Cessation-Dream or Reality! - Nessa, A; Latif, SA; Hussain, A (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2):246-247 The abstract of this article is available on the PubMed website